Metasurface-based anti-reflection coatings at optical frequencies. (16th April 2018) - Monti, Alessio; Alù, Andrea; Toscano, Alessandro; Bilotti, Filiberto
Abstract: In this manuscript, we propose a metasurface approach for the reduction of electromagnetic reflection from an arbitrary air−dielectric interface. The proposed technique exploits the exotic optical response of plasmonic nanoparticles to achieve complete cancellation of the field reflected by a dielectric substrate by means of destructive interference. Differently from other, earlier anti-reflection approaches based on nanoparticles, our design scheme is supported by a simple transmission-line formulation that allows a closed-form characterization of the anti-reflection performance of a nanoparticle array. Furthermore, since the working principle of the proposed devices relies on an average effect that does not critically depend on the array geometry, our approach enables low-cost production and easy scalability to large sizes. Our theoretical considerations are supported by full-wave simulations confirming the effectiveness of this design principle.